Significance of bacterial and white cell counts in midstream urines. - Little, P J (1980)
The results of cultures carried out on urine collected by a midstream technique (MSU) have been compared with the results of cultures of urine collected by suprapubic bladder aspiration (SPA) in the same 903 patients. Comparisons indicate that when there are more than 100 x 10(6)/l (100 000/ml) Gram-negative bacteria in the midstream urine this finding is confirmed by suprapubic aspiration in 92% of patients, and in 70% when the urine contained this number of Gram-positive bacteria. When the culture contained more than one species (mixed organisms), the presence of infection was confirmed in only 11%. When there were 10-100 x 10(6)/l bacteria in the MSU the finding of Gram-negative bacilli still indicated urinary infection in 74% of patients, but the presence of Gram-positive organisms was confirmed in only 30% and mixed organisms in 2%. In asymptomatic patients, the presence of white cells in the urine was not helpful in confirming the diagnosis of infection. The nature of the organism found in the MSU is almost as important as the number of bacteria in assessing the validity of the result.